Hygiene; Sebuah Budaya yang Terbuang namun Dirindukan - Muhamad Misbahudin; Agus Setiawan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
This paper aims to explain and explore the understanding of the Islamic boarding school community about cleanliness. This historical, anthropological research uses an ethnographic method with a postcolonial approach. The focus is on community activities in Ponorogo in applying their understanding of cleanliness. The argument of this paper is that the efforts of the people of Ponorogo in implementing cleaning activities are more of a strategy for maintaining a "real" clean cultural identity as the culture adopted by Indonesian people in general. The construction of a clean culture in the community tends to be considered outside the norms that have been standardized by the health office so that standardized patterns of cleanliness continue to be echoed in the Ponorogo community. Such a view is actually the structure of colonialism thinking, where standardization continues to discourse into different cultures of society and makes the discourse superior and worthy to be followed.